2008
DOI: 10.1111/j.1399-5618.2007.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes and the metabolic syndrome in a sample of patients with bipolar disorder

Abstract: Objectives: The presence of metabolic abnormalities is an important risk factor for cardiovascular disease and diabetes. There are limited data on the prevalence of the metabolic abnormalities in disorders other than schizophrenia in which antipsychotic medication is part of routine treatment.Methods: Sixty consecutive patients with bipolar disorder (BD) at our university psychiatric hospital and affiliate services were entered in an extensive prospective metabolic study including an oral glucose tolerance tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
3
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(115 citation statements)
references
References 46 publications
(41 reference statements)
9
94
3
6
Order By: Relevance
“…The increased prevalence of obesity in BPD patients reported in most western studies is possibly related to the dietary habits of these patients who consume more sugar and carbohydrates than controls [27,28]. The absence of an increased prevalence of MS in BPD in our study is likely to be due to lifestyle differences in the Western versus the Indian population but, to our knowledge, no study has specifically handled this issue [29]. There are studies, however, that have pointed out that some Asian population are differentially affected by IR and DM [21].…”
Section: Discussionmentioning
confidence: 50%
“…The increased prevalence of obesity in BPD patients reported in most western studies is possibly related to the dietary habits of these patients who consume more sugar and carbohydrates than controls [27,28]. The absence of an increased prevalence of MS in BPD in our study is likely to be due to lifestyle differences in the Western versus the Indian population but, to our knowledge, no study has specifically handled this issue [29]. There are studies, however, that have pointed out that some Asian population are differentially affected by IR and DM [21].…”
Section: Discussionmentioning
confidence: 50%
“…27,28 Since that time, other reports suggest even higher rates, with the prevalence of diabetes in people with SMI typically being twofold to threefold higher than age-matched samples from the general population. 10,[29][30][31][32][33][34][35] We are aware of only two large studies examining pre-diabetes among people with schizophrenia. 36,37 One study of older veterans with schizophrenia (mean age 59.6 yrs) screened for diabetes (N = 12,587, >95 % men) found that 42 % of these patients had pre-diabetes, which is comparable to 50 % of U.S. elderly adults.…”
Section: Smi and Type 2 Diabetesmentioning
confidence: 99%
“…This discrepancy is at least in part generally explained as being caused by increases in comorbid medical conditions in the mentally ill, particularly chronic illnesses such as diabetes (69) and cardiovascular disease (2, 1014). To alleviate these problems there have been reports of clinical interventions to improve health care in the seriously mentally ill with some success (15, 16).…”
Section: Objectivementioning
confidence: 99%